Editorial for the special issue on “microbiomes in extremes of aging” - Hariom Yadav; Varsha D. Badal; Michal M. Masternak; Christiaan Leeuwenburgh (Experimental Gerontology)
This special issue of the Journal of Experimental Gerontology explores the dynamic interplay between microbiomes and aging-related conditions. The four selected studies highlight the role of microbiota in Alzheimer's disease, cancer immunotherapy, myocardial infarction and tryptophan metabolism, providing insights into how microbiomes influence health and disease in aging. These studies underscore the potential for microbiome-targeted interventions to mitigate aging-related disorders and improve the quality of life for older adults.